Online shopping behavior among youth in Malaysia - Muhamad Haikal Iskandar; Nur Atieyra Sharmila Mohamad; Nurul Syakilla Ramli; Ong Li Wen; Nur Farah Diana Mohd Azlimie (2023)
The most of Malaysian younger generation are facing with financial problems because of their poor spending habits. They more prefer to engage in online shopping even though they do not have much money to do so. Additionally, people waste money by purchasing things they do not need due to lack of sense to differentiate between needs and wants. However, online shopping is still a trend as more than 26 million people in Malaysia use the internet, and 80% of consumers between the ages of 16 and 64, according to Global Web Index (2019). Therefore, this study examines the factor influencing online shopping behavior among youth in Malaysia. This research also aims to fill in the gaps in the current research and to provide new insight into the topic that focus on the youth in Malaysia. The targeted respondents for this study are youth with age 15 and 30 years old in Malaysia. A conceptual framework is projected by applying the constructs of Theory of Planned Behavior (TPB) with the factors perceived ease of use, perceived benefits and past experience. Quota sampling which is a type of non-probability sampling has been selected in this study. The research method for this study is quantitative research and the data can be quantified. Total of 400 questionnaires will be distributed to the respondents. Frequencies Analysis, Descriptive Analysis, Reliability and Validity Test and Pearson Correlation are used to analyse the data collected.